Music and Seventh Graders’ Listening Proficiency: Does Islamic song work? - Moh Nawawi Ivan; Rohmani Nur Indah (Universitas Pahlawan Tuanku Tambusai, 2021)
The use of music in teaching-learning is helpful and is not only for teachers but also students. For teachers, this music to know if the application of Islamic music in the listening class will help students improve their listening will help them to transfer their knowledge easily and in a pleasant way. While for the students, they will enjoy learning even more. The usage of the music is the use of Islamic music in listening activities. This study aims skills. This study is Classroom Action Research conducted on seventh grade high school student Pare located in Surowono Village Pare-Kediri. The research goes through the four steps, they are planning, acting, planning, and planning in one cycle. Also, three kinds of instruments are used in the study: observation, interview, and documentation. The theory used in this study is Charlotte's theory that claims that listening is one of the skills that can help students develop in learning and have basic function in communicating. This process allows for a greater measure of litigation. The result of the study pointed out that the use of Islamic music did have a positive effect on the students in that it increased their vocabulary skills and pronunciation.